Contaminant profiles of air and soil around Casey station, Antarctica; Discerning local and distant contaminant sources - Bengtson Nash, Susan; Xiao, H; Schlabach, Martin; Stark, J; King, C; Hung, H (Society for Environmental Toxicology and Chemistry (SETAC), Europe 21st Annual Meeting. Ecosystem Protection in a Sustainable World: A Challenge for Science and Regulation, 2011)
The primary input of Persistent Organic Pollutant (POP) contamination to the Antarctic is expected to be via Long Range Atmospheric Transport (LRAT) from emissions in neighboring Southern hemisphere nations In addition to LRAT, system input of POPs must increasingly consider alternate pathways Human activity in the Antarctic represents a potential direct source of both legacy and current-use chemicals It has been two decades since the organic chemical composition of air masses arriving in the Australian Antarctic Territory (AAT), which spans the majority of the eastern Antarctic sector, was last investigated Here we present the first atmospheric measurements made as part of a new continuous monitoring effort at Casey station (66°17’ S 110°31’ E), one of Australia’s all-year research stations The results are evaluated alongside POP contamination data of soil samples collected around the Casey station perimeter and the respective sample profiles are assessed for clues as to local and distant contamination sources Results suggest a potential local source of the currently produced, involatile, deca-brominated PBDE congener 209 which contributed substantially to PBDE profiles of all samples Profiles of polychlorinated biphenyls (PCBs) and rganochlorine pesticides on the other hand primarilly support LRAT as the primary input pathway of these contaminants, whilst a dominance of endosulfan in air samples evidences its ongoing application in the southern hemisphere.
Keywords: Antarktis; atmosfæren; forskningsstasjoner; forurensning; miljøgifter

Accumulation of heavy metals in an Antarctic food-chain - Lie, Elisabeth; Steinnes, Eiliv ("Heavy metals in the environment", 10th International Conference, 1995)
Keywords: Antarktis; forurensning; miljøgifter; næringskjede